Study the Effect of Temperature Variable on the Patient with Jaundice Stay Period inside the Incubator .. (Medico Legal Update, 2020)
This study is used for measuring the temperature of incubator during its used in the treatment of newborns who suffering from jaundice. The present system is characterized as low cost, easy to use and does not require a highly skilled operator, in which that used of DHT22 sensor based on the Arduino hardware platform. This system facilitates the continuous monitoring and the true knowledge of the temperature of the incubator for determination the period of stay of the child with jaundice in the hospital. In addition, the current system represents not only the possibility of knowing the temperature of the incubator but also a tool to assess the incubator’s performance, and find out the percentage of error in the temperature and the difference between the required temperature and the real temperature.